DW-Net: Dynamic Multi-Hierarchical Weighting Segmentation Network for Joint Segmentation of Retina Layers With Choroid Neovascularization - Wang, Lianyu; Wang, Meng; Wang, Tingting; Meng, Qingquan; Zhou, Yi; Peng, Yuanyuan; Zhu, Weifang; Chen, Zhongyue; Chen, Xinjian (Frontiers in Neuroscience, 2021)
Choroid neovascularization (CNV) is one of the blinding factors. The early detection and quantitative measurement of CNV are crucial for the establishment of subsequent treatment. Recently, many deep learning-based method have been proposed for CNV segmentation. However, CNV is difficult to be segmented due to the complex structure of the surrounding retina. In this paper, we propose a novel dynamic multi-hierarchical weighting segmentation network (DW-Net) for simultaneously segmentation of retina layers and CNV. Specifically, the proposed network composes of a residual aggregation encoder path for the selection of informative feature, a multi-hierarchical weighting connection for the fusion of detail information and abstract information and a dynamic decoder path. Comprehensive experimental results show that our proposed DW-Net achieves better performance than other state-of-the-art methods.